2019
DOI: 10.1002/oby.22523
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous CT‐Guided Cryovagotomy in Patients with Class I or Class II Obesity: A Pilot Trial

Abstract: Objective: This study evaluated the safety of percutaneous CT-guided cryoablation of the vagus nerve (percutaneous cryovagotomy) in participants with class I or class II obesity. Methods: The study was an open-label, single-group, prospective pilot investigation designed around safetyrelated stopping criteria. Twenty participants with 30 > BMI > 37 underwent percutaneous cryovagotomy with follow-up visits at day 7, 45, 90, and 180. Data related to adverse events, technical success, weight loss, quality of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Vagus-nerve stimulation has been used to treat a wide variety of diseases [ 6 ], most successfully implemented for the treatment of epilepsy [ 7 ], even while the mechanisms are not well understood and direct recordings of vagal activity associated with disease are not available [ 8 ]. The majority of vagal afferent fibers come from the gut [ 9 , 10 ], and abnormal vagal activity has been clearly implicated in eating and metabolic disorders [ 11 , 12 , 13 , 14 , 15 ]. In this study, we analyze the first chronic recordings of vagal spikes and the correlation of signals to several behaviors in healthy rats.…”
Section: Introductionmentioning
confidence: 99%
“…Vagus-nerve stimulation has been used to treat a wide variety of diseases [ 6 ], most successfully implemented for the treatment of epilepsy [ 7 ], even while the mechanisms are not well understood and direct recordings of vagal activity associated with disease are not available [ 8 ]. The majority of vagal afferent fibers come from the gut [ 9 , 10 ], and abnormal vagal activity has been clearly implicated in eating and metabolic disorders [ 11 , 12 , 13 , 14 , 15 ]. In this study, we analyze the first chronic recordings of vagal spikes and the correlation of signals to several behaviors in healthy rats.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the electrical modulation of the abdominal VN, the pilot study by Prologo et al is also noteworthy and showed the feasibility of percutaneous CT-guided cryovagotomy and its effectiveness in improving the mean quality of life and activity scores in class I-II obese subjects [130].…”
Section: Bm For Metabolic Disordersmentioning
confidence: 99%
“…Surgical vagotomy might effectively limit insulin secretion and induce weight loss; however, large-scale studies are missing in that respect [99]. In a pilot open-label study of percutaneous CT-guided cryovagotomy in individuals with BMI >30, 95%, the patients reported decreased appetite following the procedure, and reductions in mean absolute weight and BMI were observed at all time points up to 180 days [100].…”
Section: Hypothalamic Dysfunction In Postoperative Cp Patientsmentioning
confidence: 99%